Adaptive Organization - Management Tool in Variable Environment - Коlоsоv, A.M. (Економічний вісник Донбасу, 2014)
The article argues the notion of adaptive organization as the tool for management enterprises in variable environment. In an increasingly unstable market environment the need for decisive restructuring of enterprise management systems, perfection of all management functions, including the organization, which as a function of management, must adjust to changing conditions, that is to be adaptive. A main goal of adaptive organization of enterprise management systems is to overcome the functionalism. Thus the level of regulation the management process should decrease when variability of environment is growing. This inevitably raises the role of self-organization as in management process within enterprise as in chaotic processes in environment. If external circumstances dictate, the will of business owners or management of the companies must be to reorganize the company on the basis of decentralization. Objective parameters for assessing the need for the next step in the decentralization of the company is the share that in common transactions of the enterprise takes the unit. The current market environment is influenced of many unaccounted factors, but in the process of self-organization it moves to relatively stable states called attractors. Formally the evolution of such systems can be described by means of so-called Poincare maps. Enough successful example of an attractor that show process of variable fluctuations in sales in a supermarket on weekdays is shown in the article. As a highly successful example of an attractor show process of variable fluctuations in sales in a supermarket on weekdays. The data of these attractors are the reliable tool for planning and organizing activities.